Teori Sastra Semiotik-Feminisme dalam Novel al-Ajnihah al-Mutakassirah (Sayap-Sayap Patah) Karya Kahlil Gibran - Wulandari Wulandari (Indonesian Journal of Arabic Studies, 2019)
A literary work has strong correlation with the factors behind its. Literary work is expressed sosio-cultural background of the author, ideas and its concepts, included feminist issue, therefore that novelette al-Ajnihah al-Mutakassirah as a literary work unveiling inequality gender relations between man and woman and these was of Gibranâ€™s criticism ton feminist issues in a literary work that considered that patriarchal norms dominated various literary genres, especially Arabic literature.This study used the semiotic Michael Riffaterre analyzing a heuristic and hermeneutic approach and feminist literary criticism. Each approach used to dismantle the signs and symbols and analyse how the feminist idea of the author in the text when faced of the maleâ€™s domination and how the image of woman explored by the author, image of woman as the victims or image of woman who fight for the gender equality.In a correlation with feminism, there are many researcher had studied with the feminism approach, but according to researcher there was not one researcher study yet when feminism approach combine with semiotic study focused in teory and practise. If There, it was focus instead on Poetry. This study also focused to see a figure of Kahlil Gibran from various perspective, one of them through feminism.Â